Corrosion Protection and Biological Activity Studies for Electrochemical Polymerized Poly (N-benzothiozolyl tetrahydrophthalamic acid) on Stainless Steel Alloy - Mayasa I. Ali (Journal of Global Pharma Technology, 2019)
The present work reports the electrochemical synthesis of poly (N-benzothiozolyl tetrahydrophthalamic acid) on stainless steel 316 (S.S) which acts as working electrode by using electrochemical polymerization technique. The formed polymer film was characterized by Fourier Transform Infrared Spectroscopy (FT-IR) and Atomic Force Microscope (AFM). Corrosion protection tests for coated and uncoated S.S with polymer film were studied in 0.2 M of hydrochloric acid (HCl) solution by followed Tafel and potentiodynamic procedures. Kinetic and thermodynamic of activation parameters (Ea, A, ΔH*, ΔS* and ΔG*) were calculated. Also, investigations the effect of the synthesized polymer on some strain of bacteria a gram positive bacterium which is Staphylococcus aureus (Staph.Aure) and negative bacteria which is Escherichia coli (E.Coli). In addition the polymer film was modified with nanomaterials which are (ZnOn (nano) and Graphene).Keywords: Electrochemical polymerization, Conducting polymer, Stainless steel, Anticorrosion, Antimicrobial activity